Blocking elevated VEGF‐A attenuates non‐vasculature Fragile X syndrome abnormalities. Issue 1 (10th June 2016) - Belagodu, Amogh P.; Zendeli, Liridon; Slater, Bernard J.; Galvez, Roberto
Abstract: Fragile X syndrome (FXS) is the most common form of inherited mental retardation. In exploring abnormalities associated with the syndrome, we have recently demonstrated abnormal vascular density in a FXS mouse model (Galvan and Galvez, 2012 ). One of the most prominent regulators of vascular growth is VEGF‐A (Vascular Endothelial Growth Factor A), suggesting that FXS is associated with abnormal VEGF‐A expression. In addition to its role in vascular regulation, VEGF‐A also induces cellular changes such as increasing cell proliferation, and axonal and neurite outgrowth independent of its effects on vasculature. These VEGF‐A induced cellular changes are consistent with FXS abnormalities such as increased axonal material, dendritic spine density, and cell proliferation. In support of these findings, the following study demonstrated that FXS mice exhibit increased expression of VEGF‐A in brain. These studies suggest that increased VEGF‐A expression in FXS is contributing to non‐vascular FXS abnormalities. To explore the role of VEGF‐A in mediating non‐vascular FXS abnormalities, the monoclonal antibody Bevacizumab was used to block free VEGF‐A. Bevacizumab treatment was found to decrease FXS Synapsin‐1 expression, a presynaptic marker for synapse density, and reduce FXS testicle weight to control levels. Blocking VEGF‐A also alleviated FXS abnormalities on novel object recognition, a test of cognitive performance. These findings demonstrate that VEGF‐A is elevated in FXS brain and suggest that its expression promotes non‐vascular FXS abnormalities. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 14–25, 2017